Atmospheric chemistry of C8F17CH2CHO: Yield from C8F17CH2CH2OH (8:2 FTOH) oxidation, kinetics and mechanisms of reactions with Cl atoms and OH radicals - Chiappero, Malisa Susana (2008)
Smog chamber/FTIR techniques were used to measure a 92 ± 7% yield of C8F17CH2CHO in the chlorine atom initiated oxidation of C8F17CH2CH2OH (8:2 FTOH) in 700 Torr of air. Relative rate techniques were used to measure k(Cl + C8F17CH2CHO) = (1.9 ± 0.4) × 10-11 and k(OH + C8F17CH2CHO) = (2.0 ± 0.4) × 10-12 cm3 molecule-1 s-1 in 700 Torr of N2 or air diluent at 296 K. The results are discussed with respect to the atmospheric chemistry of fluorotelomer alcohols.